Effects of Polyunsaturated Fatty Acids (PUFA) Supplementation on Reproductive Performance of Beef Heifers Submitted to Fixed-time Artificial Insemination (FTAI) Protocol - Souza Gorges, João Batista; Gonsioroski, Andressa Varella; da Silva, Eduardo Pradebon (Acta Scientiae Veterinariae, 2019)
Background: More recently, polyunsaturated fatty acids (PUFA) supplements have been used in grazing beef herds in attempt to influence specific metabolic pathways and hormones that directly modulate reproductive function. Supplementation of calcium salts of PUFA can positively influence ovarian follicular growth, luteal function, and improve reproductive performance in dairy and beef females. The aim of this experiment was to evaluate strategies of dietary treatments using PUFA supplementation for 30 days before or after FTAI protocol and its effects on of ovulatory follicle size, ovulation, pregnancy and gestational losses rates in beef heifers. Materials, Methods & Results: One hundred and ninety-nine Brangus heifers (24 ± 3 months-old; BW= 320 ± 15 kg; BCS= 2.85 ± 0.17) were randomly assigned in three different groups to receive dietary treatments. Group 1 (n = 70) was fed with 0.5 kg/day of a protein-mineral mixture supplement containing 0.2 kg/day PUFA (Mix A)during 30 days before FTAI, Group 2 (n = 68) received the same supplement 30 days after FTAI and Control (n = 61) only the supplement without PUFA (Mix B) during all period. Heifers were submitted to estrous synchronization treatment using progesterone (P4), estradiol benzoate (E2) and prostaglandin F2a (PGF). Ultrasound exams were done to measure ovulatory follicle diameter and to determinate ovulation and pregnancy rates on Day 30 and 60 after FTAI. Daily gain (DG) was higher (P < 0.05) only when heifers received supplement containing PUFA (Group 1= 30 days prior FTAI) and (Group 2= 30 days after FTAI). PUFA supplementation before FTAI also resulted in larger ovulatory follicles diameter (P < 0.05) in Group 1 (11.2 ± 2.5 mm) compared to Group 2 (9.9 ± 2.3 mm) and Control (10.0 ± 2.07 mm). Ovulation rates were similar (P > 0.05) in Group 1 (90%), Group 2 (75%) and Control (67%). Pregnancy rates were higher (P < 0.05) in Group 1 (Day 30= 67.1% and Day 60= 64.2%) when compared with Group 2 (Day 30= 48.5% and Day 60= 44.1%) and Control (Day 30= 49.2% and Day 60= 45.9%). Gestation losses were similar (P > 0.05) among Groups 1 (6.6%), 2 (9%) and Control (6.6%). Discussion: Rumen-protected supplemental lipids have been used to increase energy density and to determine direct positive effects on reproduction in dairy and beef herds. There is evidence that feeding moderate amounts of PUFA supplements can improve energy status and result in significant differences in DG as it was observed during experimental period. Thus, heifers that received 0.2 kg/day of PUFA supplement 30 days before FTAI protocol had also a positive effect on ovulatory follicles size, but ovulation rates were similar in groups. Beneficial effects of pre-breeding PUFA supplementation were observed on pregnancy rates on Days 30 and 60 after FTAI, but pregnancy loss was not different among dietary treatments in beef heifers. Based on this study, PUFA supplementation before FTAI protocol had a positive effect on reproductive performance of beef heifers by directly improving ovarian function, uterine environment and early embryonic development. Results indicate that pre-breeding PUFA supplementation to beef heifers is a suitable strategy to increase pregnancy rate in FTAI programs. Therefore, for a better understanding of interactions of nutritional strategies and utero-ovarian functions more evaluations are needed to understand the mechanisms by which feeding PUFA may improve reproductive function in beef heifers.